Donor Darah dalam Pandangan Islam: Kajian Studi Literatur - Nurmayani Nurmayani; Nisaul Zahra; Aini Riza Gambari; Riski Ainaul Mardhiyah; Jasmin Novi Ramadhani Nasution (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
In the Islamic perspective, blood donation is not only viewed from a medical perspective, but also from the perspective of sharia law and ethics that regulate the treatment of blood and the human body. This study aims to comprehensively examine the law, ethics, and benefits of blood donation according to Islamic perspective, and to provide a systematic understanding in order to eliminate doubts in the Muslim community regarding the issue of blood donation. This study uses a qualitative method with a literature study approach. Data were collected from various library sources such as books, journal articles, fatwas, and relevant official documents, then analyzed descriptively-qualitatively to identify the main themes related to the law and ethics of blood donation in Islam. The results of the study show that the majority of scholars allow blood donation in emergency conditions to save lives, based on the fiqh principle of ad-darurat tubihul mahzurat (emergency conditions allow what is forbidden) and maqasid sharia (hifz al-nafs/protecting the soul). Blood donation is also considered a highly recommended social charity and worship, and can even reach the level of fardhu kifayah, as long as it does not endanger the donor and is done sincerely. In addition, blood donation has health benefits for both donors and recipients.